PENGARUH SALES PROMOTION, HEDONIC SHOPPING MOTIVATION, DAN SHOPPING LIFESTYLE TERHADAP IMPULSE BUYING PADA SITUS BELANJA ONLINE (STUDI TERHADAP PENGGUNA TOKOPEDIA DI KOTA SEMARANG) - MIFTA MUTIARA S; Ali Maskur (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2023)
In this digital era, humans are very dependent on hand-held devices that are easy to carry anywhere. It includes online shopping site applications, one of which is Tokopedia. Without any restrictions, humans can do anything, including impulse buying or spontaneous purchases. A research aim was to observe the impact of sales promotion, hedonic shopping motivation, and shopping lifestyle of impulse buying on online shopping sites in Semarang City. This research used approach of quantitative with a purposive sampling technique. An explanation of the influence and significance of the variables is obtained by means of multiple linear regression analysis. This research proves the proceeds that sales promotion has negative impact and not significant to impulse buying. Either hedonic shopping motivation or shopping lifestyle have positively impacted and significance to the impulse buying.